2008
DOI: 10.1371/journal.pone.0002681
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Shedding of the NMDA Receptor Glycine Binding Site by Matrix Metalloproteinase 3: A PUTATIVE Mechanism of Postsynaptic Plasticity

Abstract: Functional and structural alterations of clustered postsynaptic ligand gated ion channels in neuronal cells are thought to contribute to synaptic plasticity and memory formation in the human brain. Here, we describe a novel molecular mechanism for structural alterations of NR1 subunits of the NMDA receptor. In cultured rat spinal cord neurons, chronic NMDA receptor stimulation induces disappearance of extracellular epitopes of NMDA receptor NR1 subunits, which was prevented by inhibiting matrix metalloproteina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…However, Western blot analysis of pro-and mature BDNF levels were not found to be prominently altered in MMP-3 −/− cerebella (data not shown), indicating that BDNF might not be the major MMP-3 substrate responsible for the observed cerebellar phenotype in MMP-3 −/− mice. Other substrates out of the very broad MMP-3 degradome and known to be involved in parallel fiber outgrowth and/or GC migration are vitronectin, NMDA receptors, and MMP-9 [1,5,7,38,[45][46][47]. Although MMP-9 shows a resembling mRNA and protein expression profile in the developing cerebellum and modulates GC exit from the EGL, MMP-9 deficiency or inhibition is known to affect GC apoptosis and reduce parallel fiber outgrowth, processes which were not affected or opposite in MMP-3 −/− animals [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…However, Western blot analysis of pro-and mature BDNF levels were not found to be prominently altered in MMP-3 −/− cerebella (data not shown), indicating that BDNF might not be the major MMP-3 substrate responsible for the observed cerebellar phenotype in MMP-3 −/− mice. Other substrates out of the very broad MMP-3 degradome and known to be involved in parallel fiber outgrowth and/or GC migration are vitronectin, NMDA receptors, and MMP-9 [1,5,7,38,[45][46][47]. Although MMP-9 shows a resembling mRNA and protein expression profile in the developing cerebellum and modulates GC exit from the EGL, MMP-9 deficiency or inhibition is known to affect GC apoptosis and reduce parallel fiber outgrowth, processes which were not affected or opposite in MMP-3 −/− animals [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have indicated that under special conditions, such as inflammatory or degenerative diseases of the central nervous system, matrix metalloproteinases cleave the NR1a subunit at the extracellular NH 2 -terminal domain and modify NMDA receptor function (36,37). Tissue-type plasminogen activator is also known to bind to and then cleave the ATD of the NR1 subunit at arginine 260, which serves as a necessary step to enhance NMDA receptor signaling in neurons (38,39).…”
Section: Nr2a Atd Contains An Er Retentionmentioning
confidence: 99%
“…Interestingly, it has been reported that NMDAR has been found to associate with metabotropic dopamine receptors [149]. There is also a possibility that Ca 2+ flux-independent metabotropic-like NMDAR function could be the result of proteolytic cleavage, as that already reported for NMDAR subunit GluN1 [150], that occurs to other membrane molecules [151]. In addition, GluN2C subunit-mediated IC signaling, found highly expressed in most transcriptome analysis of astrocytes, but that has been poorly studied, could be involved.…”
Section: Insights Regarding Astrocytic Nmdarmentioning
confidence: 81%